2021
DOI: 10.3390/s22010158
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Atmospheric Laminar Channels: Experimental Results and Method Dissemination

Abstract: In this paper, a practical application of theoretical developments found in our previous works is explored in relation to atmospheric lidar data. Multifractal structures, previously named “laminar channels”, have been identified in atmospheric profiles—these exhibit cellular and self-structuring properties, and are spatially ordered across the atmospheric profile. Furthermore, these structures have been connected to the spontaneous emergence of turbulent behavior in the calm atmospheric flow. Calculating the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The existence of such channels has already been demonstrated in these studies, but now a different and synergic theoretical justification has been produced for them with the previously demonstrated emergence of nonlinear behaviors in the dynamics of the atmosphere [20,21]. Our previous papers show that a scale transition model can be coupled with a discontinuous form of the Navier-Stokes equation to produce a type of logistic map [21]. Given the occurrence of both chaos and order in this map with the existence of Pomeau-Maneville areas, it was shown that it is possible to identify quasi-laminar or fully laminar regions in atmospheric profiles, leading to "laminar channel" structures that show either ascending or descending behavior [21].…”
Section: Madelung-type Scenario In the Description Of Atmospheric Dyn...mentioning
confidence: 92%
See 2 more Smart Citations
“…The existence of such channels has already been demonstrated in these studies, but now a different and synergic theoretical justification has been produced for them with the previously demonstrated emergence of nonlinear behaviors in the dynamics of the atmosphere [20,21]. Our previous papers show that a scale transition model can be coupled with a discontinuous form of the Navier-Stokes equation to produce a type of logistic map [21]. Given the occurrence of both chaos and order in this map with the existence of Pomeau-Maneville areas, it was shown that it is possible to identify quasi-laminar or fully laminar regions in atmospheric profiles, leading to "laminar channel" structures that show either ascending or descending behavior [21].…”
Section: Madelung-type Scenario In the Description Of Atmospheric Dyn...mentioning
confidence: 92%
“…Now, in order to consider and develop the implications of the theory discussed thus far, we refer to our previous works in which the theoretical and practical foundations of what is known as "laminar channels" were made [20,21]. The existence of such channels has already been demonstrated in these studies, but now a different and synergic theoretical justification has been produced for them with the previously demonstrated emergence of nonlinear behaviors in the dynamics of the atmosphere [20,21]. Our previous papers show that a scale transition model can be coupled with a discontinuous form of the Navier-Stokes equation to produce a type of logistic map [21].…”
Section: Madelung-type Scenario In the Description Of Atmospheric Dyn...mentioning
confidence: 99%
See 1 more Smart Citation